FPA Optimized Selective Harmonic Elimination in Symmetric-Asymmetric Reduced Switch Cascaded Multilevel Inverter - Panda, Kaibalya Prasad; Bana, Prabhat Ranjan; Panda, Gayadhar (IEEE transactions on industry applications, 2020)
Symmetrical and asymmetrical multilevel inverters (MLIs) have demonstrated its usefulness in a wide range of applications. This is accomplished due to the ongoing improvement by reducing the converter size and enhancement in the voltage quality. In this article, a generalized cascaded MLI structure is developed, which can operate in both symmetric and asymmetric modes. Comparative assessment in terms of the number of components and voltage stress warrants the design superiority. A new selective harmonic elimination (SHE) control using flower pollination algorithm (FPA) is investigated for the developed asymmetrical MLI. The salient features of the FPA such as less burdensome compilation and ability tos single-stage local and global search ascertain the elimination of the targeted harmonics through optimum angles computation. Moreover, the competence of the FPA is verified by comparing it with well-known SHE algorithms. Simulation analysis is carried out in MATLAB/Simulink environment, which validates the workability of the developed system. Experimental tests using fundamental and high switching frequency control techniques are further conducted under a dynamic environment to demonstrate the efficacy of the proposed methodology.